2005
DOI: 10.1016/j.femsle.2005.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Identification of σV-dependent genes ofBacillus subtilis

Abstract: The chromosome of Bacillus subtilis codes for seven extracytoplasmic function sigma factors the activity of which is modulated normally by a cognate anti-sigma factor. While inducing factors and genes for four of them (sigma(M), sigma(W), sigma(X), and sigma(Y)) have been identified, those of the remaining three sigma factors including sigma(V) remain elusive. The objective of the present study was the unequivocal identification of its anti-sigma factor and of genes controlled by sigma(V). In many cases report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…No regulatory overlap was observed with any other ECF factors, and its physiological role is unclear. Interestingly, genes activated by the overexpression of V have been identified, and most appear to overlap with the known targets for M , W , and X (39). Thus, V may, under some growth conditions, also contribute to expression of some of the same genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No regulatory overlap was observed with any other ECF factors, and its physiological role is unclear. Interestingly, genes activated by the overexpression of V have been identified, and most appear to overlap with the known targets for M , W , and X (39). Thus, V may, under some growth conditions, also contribute to expression of some of the same genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some targets of ECF factor regulation have promoter sites that are recognized in vitro and, apparently, also in vivo by more than one holoenzyme species (9,20). A recently described list of putative V -dependent genes almost completely overlaps with genes that have already been shown to be under the control of M , W , or X (39). In light of this potentially significant regulatory overlap, it seems likely that the lack of dramatic phenotypes associated with null mutations in many ECF factor genes in B. subtilis may be due, in part, to redundancy.…”
mentioning
confidence: 97%
“…The B. subtilis bcrC gene was known to be directly regulated by three extracytoplasmic function sigma factors: SigX, SigM, and SigV (4,18,35). It is now clear that SigI is the fourth sigma factor that can directly regulate bcrC expression.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether sigI overexpression could stimulate expression of these candidate target genes, PCR-amplified DNA fragments containing putative I promoter elements of these candidate genes were individually cloned into the promoter probe vector pDL (34), which was designed to create transcriptional fusions to bgaB (encoding a thermostable ␤-galactosidase). It was previously shown that the bcrC gene could be directly regulated by three extracytoplasmic function sigma factors: SigX, SigM, and SigV (4,18,35). Therefore, the DNA fragment used in this report did not include the X , M , and V promoter regions so as to avoid possible interference.…”
Section: Effects Of Overexpression Of B Subtilis Sigi On Expression mentioning
confidence: 99%
“…Expression of the yqjL gene, for example, appears from lacZ reporter fusions to be almost completely dependent on SigM, and yet its promoter was recognized by SigW and SigX in in vitro runoff transcription experiments (8). The bcrC and ypuA genes were very strongly induced in a strain in which the ECF sigma factor SigV was released from anti-sigma factor control (29). The presence of multiple promoters for all the sigM-regulated genes examined, the potential for recognition of the same promoter sequence by multiple ECF sigma factors, and the potential for different levels of activity of such sigma factors under various stress conditions together generate a complexity of regulation that makes a specific and individual role for this sigma factor in cell growth and envelope maintenance difficult to define.…”
Section: Vol 189 2007 Notes 4535mentioning
confidence: 99%